Neutralizing Anti-Rituximab Antibodies and Relapse in Membranous Nephropathy Treated With Rituximab - Boyer-Suavet, Sonia; Andreani, Marine; Lateb, Maël; Savenkoff, Benjamin; Brglez, Vesna; Benzaken, Sylvia; Bernard, Ghislaine; Nachman, Patrick H.; Esnault, Vincent; Seitz-Polski, Barbara (Frontiers in Immunology, 2020)
Membranous Nephropathy (MN) is an autoimmune disease associated with antibodies against podocyte proteins: M-type phospholipase A2 receptor (PLA2R1) or thrombospondin type-1 domain-containing 7A (THSD7A) in 70% and 3% of patients, respectively. Antibody titer is correlated with disease activity. Therefore, decreasing PLA2R1-Antibodies titer has become an important goal of therapy. Rituximab a chimeric monoclonal antibody induces remission in 60-80% of MN patients. All monoclonal antibodies such as rituximab can elicit antidrug antibodies, which may interfere with therapeutic response. We aim to analyze the relevance of anti-rituximab antibodies on the outcome of MN after a first course of rituximab. Forty-four MN patients were included and treated with two 1g infusions of rituximab at 2-week interval. Anti-rituximab antibodies, CD19 count, and clinical response were analyzed. Then, we (i) analyzed the association of anti-rituximab antibodies at month-6 with response to treatment: remission, relapse and the need for another rituximab course; (ii) confirmed if anti-rituximab antibodies could neutralize rituximab B-cells depletion and (iii) tested whether anti-rituximab antibodies could cross-inhibit new humanized anti-CD20 therapies. Anti-rituximab antibodies were detected in 10 patients (23%). Seventeen patients received a second rituximab course after a median time of 12 months [7-12], following nine cases of resistance and eight relapses. Anti-rituximab antibodies were significantly associated with faster B-cell reconstitution at month-6 (75 [57-89] vs 2 [0-41] cells/μl, p=0.006), higher proteinuria 12 months after rituximab infusion (1.7 [0.7; 5.8] vs 0.6 [0.2; 3.4], p=0.03) and before treatment modification (3.5 [1.6; 7.1] vs 1.7 [0.2; 1.7] p=0.0004). Remission rate 6 months after rituximab was not different according to anti-rituximab status (p>0.99) but the rate of relapse was significantly higher for patients with anti-rituximab antibodies (p<0.001). These patients required more frequently a second course of rituximab infusions (7/10 vs 10/34, p=0.03). Anti-rituximab antibodies neutralized rituximab activity in 8/10 patients and cross-reacted with other humanized monoclonal antibodies in only two patients. Three patients with anti-rituximab antibodies were successfully treated with ofatumumab. Anti-rituximab antibodies could neutralize rituximab B cells cytotoxicity and impact clinical outcome of MN patients. Humanized anti-CD20 seems to be a satisfying therapeutic alternative for patients with anti-rituximab antibodies and resistant or relapsing MN.